4D printing of adaptable “living” materials based on alkoxyamine chemistry - Tran, Hoang Bao Duc; Vázquez-Martel, Clara; Catt, Samantha; Jia, Yixuan; Tsotsalas, Manuel; Spiegel, Christoph A.; Blasco, Eva (Advanced functional materials, 2024)
4D printing has emerged as a powerful strategy capable of revolutionizing additive manufacturing by enabling objects to dynamically transform overtime on demand. Despite significant progress, the full potential remains unrealized, particularly in the utilization of dynamic covalent chemistry. This study introduces a new approach using a multifunctional cross-linker with alkoxyamine functionalities for 4D printing. Digital light processing (DLP) is employed for high-resolution printing of complex objects. Leveraging alkoxyamine bonds' dynamic and living characteristics, the printed structures can be further modified through nitroxide-mediated polymerization (NMP) using styrene and nitroxide exchange reactions (NER). The resulting “living” printed structures exhibit the unique ability to undergo both “growth” and “degrowth”, dynamically adapting their size as well as the reduced Young's Modulus across a wide range (770 kPa-1.2 GPa). The chain extension by NMP and softening by NER are carefully characterized by IR and EPR spectroscopy. The presented approach opens avenues for the development of 4D printed structures with complex adaptive systems, showcasing enormous potential in a wide range of fields.